2020
DOI: 10.1021/acs.nanolett.0c01956
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically Tunable Quantum Interference in Ferrocene-Based Single-Molecule Junctions

Abstract: Ferrocenes are ubiquitous organometallic building blocks that comprise a Fe atom sandwiched between two cyclopentadienyl (Cp) rings that rotate freely at room temperature. Of widespread interest in fundamental studies and real-world applications, they have also attracted some interest as functional elements of molecular-scale devices. Here we investigate the impact of the configurational degrees of freedom of a ferrocene derivative on its single-molecule junction conductance. Measurements indicate that the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(86 citation statements)
references
References 40 publications
5
65
1
Order By: Relevance
“…Quantum interference (QI) in electron transport of singlemolecule devices is a phenomenon that takes place when two or more pathways of electrons are in phase or out of phase. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] In clear contrast with the double-slit interference of light or electrons for which the interference patterns are observed in real space, quantum interference in electron transport studied here happens in the energy space and is typically accompanied by the increase or decrease of the transmission function in a certain energy range. [19][20][21] In particular, the case of destructive quantum interference (DQI) is characterized by a sharp dip in the transmission function, which leads to a decrease of transmission by several orders of magnitude.…”
Section: Introductionmentioning
confidence: 80%
“…Quantum interference (QI) in electron transport of singlemolecule devices is a phenomenon that takes place when two or more pathways of electrons are in phase or out of phase. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] In clear contrast with the double-slit interference of light or electrons for which the interference patterns are observed in real space, quantum interference in electron transport studied here happens in the energy space and is typically accompanied by the increase or decrease of the transmission function in a certain energy range. [19][20][21] In particular, the case of destructive quantum interference (DQI) is characterized by a sharp dip in the transmission function, which leads to a decrease of transmission by several orders of magnitude.…”
Section: Introductionmentioning
confidence: 80%
“…For example, the angle between alkane chains and an electrode substrate in monolayer-based junctions can determine the relative contributions of through-bond and through-space (chain-to-chain) tunneling 1,2 . For single molecule junctions, the electrode-molecule-electrode angle in a ferrocene-based junction tunes quantum conductance interference 3 , and tilting a benzene molecule between nickel electrodes changes magnetoresistance in a non-monotonic way 4 . Generally, in break junction experiments that study the conductance of a molecule attached between two electrodes, it was shown that as the distance between the two electrodes changes, the bridging molecule may change its orientation, leading to considerable variations in the conductance properties of the junction [5][6][7][8][9][10][11][12] .…”
Section: Bodymentioning
confidence: 99%
“…Electronic states and spin states in single-molecule junctions have been manipulated, e.g. by gate electrodes 2–4 or mechanically, 5–11 profiting from the precise control of electrode distances in scanning tunneling microscope break junction and MCBJ experiments. Stacked benzene rings offer interesting opportunities for mechanical manipulation of charge transport, and recently they have been explored both theoretically 12–17 and experimentally, first in rings held together by van der Waals forces 6,9 and thereafter with rings covalently connected by alkyl bridges in paracyclophanes.…”
Section: Introductionmentioning
confidence: 99%